(untitled) (Eurasian Research Bulletin, 2022)
This article reveals the impact of pesticides on the free radicals in mammalian blood and on the paramagnetic centers. It has been discovered first time that pesticides ability to increase the quantity of free radicals, the influence of pesticides together with nitrates on the change of the paramagnetic centers of blood.